Morphological and morphometric analysis of glenoid cavity of dry human scapula - Shakya, Shuvechha; Yadav, Shekhar Kumar; Shrestha, Anusuya; Shrestha, Amit (Janaki Medical College Journal of Medical Science, 2026)
Background & Objectives: One of the important joints in human body is the Shoulder Joint. The glenoid cavity of scapula articulates with the head of humerus to form the shoulder joint. An understanding of normal glenoid cavity is important to analyze the stability of the glenohumeral joint, to design prostheses for shoulder arthroplasty, so this study was done to observe the morphological features of the glenoid cavity of dry scapula. Materials and Methods: A college based observational cross-sectional descriptive study was carried out on all 50 dry scapulae (22 right and 28 left) of unknown age and sex available in the Department of Anatomy, of Chitwan Medical College Teaching Hospital, Chitwan, Nepal. Required bony landmarks were well identified, marked and different parameters of glenoid cavity were measured using digital vernier calliper (Precision Tool Corporation, Pune, Maharashtra, India: 150mm/6 inch; Stainless Steel Hardened Model). For observing the shape, the edge of glenoid cavity was highlighted with coloured chalk. Statistical analysis was done using SPSS 21 software and the findings were reported as frequency and distribution. Results: In the current study, pear shaped glenoid cavity (62%) were most frequently seen, followed by oval shape glenoid cavity (28%). Inverted comma (5%) was the shape that was least observed. The results also illustrated that the superior-inferior glenoid cavity diameter of right side was 34.87± 2.50 mm and 36.48±1.97 mm on left side. The average anterior- posterior diameter (Anterior –Posterior 1 and Anterior- Posterior 2) of right glenoid cavity was 24.47±1.54 mm and 17.47± 1.56 mm and that of left side was 25.45± 1.35 and 18.74± 1.17mm. The average glenoid cavity index on right side was 70.05± 2.42 mm and that of left side was 69.77± 2.41 mm. Conclusions: The knowledge about the diverse shape and dimensions of glenoid are highly crucial during designing and fitting of glenoid component for total shoulder arthroplasty. It is also useful when evaluating a variety of clinical diseases, such as Bankart lesions, osteochondral abnormalities, and rotator cuff illness.